Gyraulus elenae sp. n.—a new Planorbid snail from Eastern Turkey (Mollusca: Gastropoda: Planorbidae) - Vinarski, Maxim V.; Glöer, Peter; Palatov, Dmitry M. (Zootaxa, 2013)
The most recent complete list of the basommatophoran snails of Turkey (Yildirim et al., 2006) includes eight species of the genus Gyraulus Charpentier, 1837 (sensu Meier-Brook, 1983). Four of them have wide Palearctic or even Holarctic distribution, whereas the rest are of the Mediterranean – Near Eastern type of distribution. However, this species list is clearly far from completeness as recently several new species of Gyraulus have been recorded for Turkey, including four species (Gyraulus pamphylicus Glöer et Rähle, 2009, G. nedyalkovi Glöer et Georgiev, 2012, G. egridirensis Glöer et Girod, 2013, and G. taseviensis Glöer et Girod, 2013) described as new for science. In this note, we describe one more Gyraulus species from waterbodies of Eastern Turkey and provide a determination key for all species of the genus recorded hitherto from Turkey.